2021
DOI: 10.3390/antibiotics10040374
|View full text |Cite
|
Sign up to set email alerts
|

Potential Environmental and Human Health Risks Caused by Antibiotic-Resistant Bacteria (ARB), Antibiotic Resistance Genes (ARGs) and Emerging Contaminants (ECs) from Municipal Solid Waste (MSW) Landfill

Abstract: The disposal of municipal solid waste (MSW) directly at landfills or open dump areas, without segregation and treatment, is a significant concern due to its hazardous contents of antibiotic-resistant bacteria (ARB), antibiotic resistance genes (ARGs), and metal resistance genes (MGEs). The released leachate from landfills greatly effects the soil physicochemical, biological, and groundwater properties associated with agricultural activity and human health. The abundance of ARB, ARGs, and MGEs have been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 157 publications
1
56
0
Order By: Relevance
“…Farm bioaerosols generated during farming practices have also been regarded as a reservoir of ARB and ARGs and may pose a high risk to animal and human health ( McEachran et al, 2015 ; Van Leuken et al, 2016 ; Anand et al, 2021 ; Gwenzi et al, 2022 ). Bai et al (2021) investigated the spread of ARB from animal bioaerosols and found that ARB and ARGs in bioaerosols could easily be transmitted from animal farms to the environmental dust through the natural wind.…”
Section: Potential Risks Of Antibiotic Resistance In Food Animal Farmsmentioning
confidence: 99%
“…Farm bioaerosols generated during farming practices have also been regarded as a reservoir of ARB and ARGs and may pose a high risk to animal and human health ( McEachran et al, 2015 ; Van Leuken et al, 2016 ; Anand et al, 2021 ; Gwenzi et al, 2022 ). Bai et al (2021) investigated the spread of ARB from animal bioaerosols and found that ARB and ARGs in bioaerosols could easily be transmitted from animal farms to the environmental dust through the natural wind.…”
Section: Potential Risks Of Antibiotic Resistance In Food Animal Farmsmentioning
confidence: 99%
“…They can also be in a variety of shapes and materials (Alimi et al 2018). As a result of the researches, it is seen that MP pollution has become an increasing threat, especially in the aquatic environment (Zhou et al 2020) and in landfills (Anand et al 2021). MPs have been found in more than 600 species of organisms (Toussaint et al 2019), in human food such table salt (Peixoto et al 2019), beer (Kosuth et al 2018) and drinking water (Mason et al 2018) on all continents including the America (McEachern et al 2019), Antarctica (Bessa et al 2019), Europe (Sadri & Thompson 2014), and Asia (Sarkar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…About the solid wastes originating from the manufacturing process of PPCPs, they are typically discarded into landfills and garbage dump sites or incinerated. Landfill waste disposal is commonly practised in developing countries, notwithstanding its negative health and environmental impacts, because it is the cheapest method to dispose of solid wastes that are generated (Bong et al 2017 ; Anand et al 2021a , b , c , d ).…”
Section: Occurrencementioning
confidence: 99%
“…Some patients even have to stay for an extended period in hospitals before they can fully recover. The utilization of hospitals in some cities across the globe has even reached critical levels with the advent of the COVID-19 pandemic in the latter part of 2019 (Adelodun et al 2021a , b , c , d ; Anand et al 2021a , b , c , d ) and the succeeding waves of infection. Patients who suffer from severe symptoms of the disease need a longer time to convalesce.…”
Section: Occurrencementioning
confidence: 99%